STUDENTS’ PERCEPTION OF 21st CENTURY SKILLS DEVELOPMENT THROUGH THE IMPLEMENTATION OF PROJECT-BASED LEARNING - Ayu Fatmawati (State Institute for Islamic Studies IAIN of Metro, 2018)
The phenomenon of graduate students who are not ready for employment in a digital age seizes the educators’ attention. Then, some research findings identified the students’ need to focus on 21st century skills in order to fulfill the workplace requirements. Some teaching methods are provided to help teacher in teaching 21st century skills. One of them is the project based learning (PbL). This research aimed at knowing the students’ perception of 21st century skill development through the implementation of project-based learning. Descriptive quantitative method was utilized in this research. The respondents were the students of English department from one of private universities in East Java. An online questionnaire was used as the instrument in this research. The data analysis was done statistically. The responses indicate that the implementation of project based learning generally helps the students in developing their 21st century skills. In conclusion, the students agree that the PbL can develop their 21st century skills. So, the lecturers are suggested to design the project based learning with the specific goals of 21st century skills development.